The Easterlin paradox of entrepreneurs during China's economic transition - Jidong Yang; Yunqi Zeng; Qing Wang (International Studies of Economics, 2023)
Abstract This paper investigates the determinants and the time pattern of the subjective well‐being of private business owners. We find that both personal and enterprise‐level factors have a significant influence on subjective status of private business owners. Meanwhile, we find supportive evidence of Easterlin paradox among Chinese private entrepreneurs: both personal income and operating revenue enhance subjective status in a certain period, but subjective status declines as time goes by, even as incomes continue to rise. A further Oaxaca–Blinder decomposition suggests that the competition and provincial factors are the keys to explaining the paradox. Finally, we try to verify the positive effect of political connection on entrepreneurs' subjective status to provide some helpful advice for the government.